Bifunctionalized chitosan: A versatile adsorbent for removal of Cu(II) and Cr(VI) from aqueous solution. (1st December 2018) - Moreira, Ana Luísa da Silva Lage; Pereira, Analice de Souza; Speziali, Marcelo Gomes; Novack, Kátia Monteiro; Gurgel, Leandro Vinícius Alves; Gil, Laurent Frédéric
Graphical abstract: Highlights: Bifunctionalized chitosan(C4) was synthesized for removal of both Cu 2+ and Cr 6+ . C4 was insoluble in water in a pH range of 1–10. The maximum adsorption capacity of C4 for Cu 2+ adsorption at pH 5.5 was 2.60 mmol/g. The maximum adsorption capacity of C4 for Cr 6+ adsorption at pH 2.0 was 3.50 mmol/g. The re-adsorption efficiency of C4 was 106% for Cu 2+ and 44% for oxyanions of Cr 6+ . Abstract: This study describes the chemical modification of chitosan to produce a novel bifunctionalized adsorbent material (C4 ) for the removal of Cu 2+ and oxyanions of Cr 6+ from a single aqueous solution. The chemical modifications allowed C4 to be insoluble under acidic conditions, improving the chemical properties of the modified chitosan in aqueous solution. C4 adsorbent was synthesized by reaction of the amino group of chitosan with 2-pyridinecarboxaldehyde, a reduction of imine group, followed by esterification with EDTA dianhydride (EDTAD). C4 was characterized by solid-state 13 C nuclear magnetic resonance, infrared spectroscopy, and elemental analysis. The adsorption studies of Cu 2+ and oxyanions of Cr 6+ in a batch mode were evaluated as a function of the contact time (kinetics), solution pH, and initial metal ion concentration. The maximum adsorption capacities ( Q max ) of C4 for the adsorption of Cu 2+ (pH 5.5) and Cr 6+ (pH 2.0) were 2.60 and 3.50 mmol/g, respectively. The reusability of the recovered C4 adsorbent was also evaluated.